Sequential bacterial sampling of the midline incision in horses undergoing exploratory laparotomy. (17th May 2018) - Isgren, C. M.; Salem, S. E.; Townsend, N. B.; Timofte, D.; Maddox, T. W.; Archer, D. C.
Summary: Background: There is limited information about bacterial isolates that are present on the equine midline incision during and following exploratory laparotomy. Objectives: To investigate the bacterial species cultured from the ventral midline pre‐, intra‐ and post‐ laparotomy, whether particular bacterial isolates are associated with the development of surgical site infections (SSIs) and to report the antimicrobial resistance phenotypes of these isolates. Study design: Prospective cohort study. Methods: The ventral midline of 31 horses undergoing exploratory laparotomy was sampled for bacterial culture at set time‐points pre, intra and post‐operatively. Inclusion criteria were that horses must have undergone exploratory laparotomy within 90 min of the initial colic examination upon hospital admission and must not have been placed in a stable prior to surgery. SSI was defined as any purulent or serous discharge from the laparotomy incision of >24 h duration. Results: Seven horses (22.6%) developed a SSI. None of the variables tested were associated with the altered risk of SSI. The prevalence of a positive bacterial culture from the incision increased progressively over time and a variety of bacteria were isolated. A positive intra‐operative culture was not a predictor of SSI; and when a SSI did occur, it was due to a different bacterial isolate. MRSA and ESBL‐producers were identified in the post‐operative period in one and four different horses respectively, but none of these developed a SSI. Main limitations: Sampling was limited to hospitalisation and no culture results were available for horses developing SSI following hospital discharge. Conclusions: A variety of bacterial species may be isolated from equine laparotomy incisions peri‐operatively without development of SSI. SSI does not appear to be solely related to bacterial contamination of the incision peri‐operatively and other mechanisms such as bacteraemia merit further investigation.